SOSIALISASI PELATIHAN PENGGUNAAN APLIKASI CORELDRAW UNTUK DESAIN KEMASAN DAN SOSIAL MEDIA MARKETING PADA USAHA ROTI DI KOTA DENPASAR - I Putu Widyarsana; Putu Eny Suhardiyani (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are types of businesses operated on a small scale and not part of a larger corporation. MSMEs play a vital role and are often utilized by the government to address issues such as reducing the unemployment rate. In MSMEs, the role of technology becomes a much-needed solution, particularly in marketing and product innovation development. The partner in this community service project is Mrs. Kamaryanti, who sells a variety of breads and cakes. This business has been running for approximately three years. She makes the bread at her home located in Peguyangan Kangin Village, North Denpasar. Her customers include schools and small shops/stalls in the surrounding area. Based on observations and interviews, the partner has not yet implemented digital marketing, so sales are still conducted traditionally. The business is known to the public primarily through previous buyers and the local community. As a result, the small-scale marketing efforts have not been optimal. In reality, today’s MSME entrepreneurs must stay updated and continuously adapt to technological developments by implementing online sales, which can help increase the sales of Mrs. Kamaryanti's bread and cake business. Additionally, the partner does not have product packaging design that serves as brand identity. Attractive packaging designs can assist with product marketing because they include important information such as the business name, type of product, product label, and the producer’s address, allowing customers to distinguish this brand from others. Based on the partner’s situation, the community service team provided training on the use of CorelDRAW software to design product packaging. Meanwhile, the application of social media marketing was carried out using Instagram and Facebook. The expected outcomes of this community service are that the partner can increase sales, expand the sales area, and make it easier for consumers to recognize the products offered